Comparison of athlete-coach perceptions of internal and external load markers for elite junior tennis training - Murphy, A.; Duffield, R.; Kellett, A.; Reid, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: To investigate the discrepancy between coach and athlete perceptions of internal load and notational analysis of external load in elite junior tennis. Methods: Fourteen elite junior tennis players and 6 international coaches were recruited. Ratings of perceived exertion (RPE) were recorded for individual drills and whole sessions, along with a rating of mental exertion, coach rating of intended session exertion, and athlete heart rate (HR). Further, total stroke count and unforced error count were notated using video coding following each session, alongside coach and athlete estimations of shots and errors made. Finally, regression analyses explained the variance in the criterion variables of athlete and coach RPE. Results: Repeated measures analyses of variance and interclass correlation coefficients revealed that coaches significantly (p<0.01) underestimated athlete session-RPE, with only moderate correlation (r=0.59) demonstrated between coach and athlete. However, athlete drill-RPE (p=0.14; r= 0.71) and mental exertion (p=0.44; r= 0.68) were comparable and substantially correlated. No significant differences in estimated stroke count were evident between athlete-coach (p=0.21), athletenotational analysis (p=0.06), or coach-notational analysis comparison (p=0.49). Coaches estimated significantly greater unforced errors than either athletes or notational analysis (p<0.01). Regression analyses found that 54.5% of variance in coach RPE was explained by intended session exertion and coach drill-RPE, while drill-RPE and peak HR explained 45.3% of the variance in athlete session-RPE. Discussion: Coaches misinterpreted session-RPE but not drill-RPE, whilst inaccurately monitoring error counts. Improved understanding of external and internal load monitoring may assist coach-athlete relationships in individual sports like tennis to avoid maladaptive training.